2023
DOI: 10.1088/1748-9326/acb837
|View full text |Cite
|
Sign up to set email alerts
|

Building a bridge: characterizing major anthropogenic point sources in the South African Highveld region using OCO-3 carbon dioxide snapshot area maps and Sentinel-5P/TROPOMI nitrogen dioxide columns

Abstract: In this paper, we characterize major anthropogenic point sources in the South African Highveld region using Orbiting Carbon Observatory-3 (OCO-3) Snapshot Area Map (SAM) carbon dioxide (CO2) and Sentinel-5 Precursor (S5P) TROPOspheric Monitoring Instrument (TROPOMI) nitrogen dioxide (NO2) observations. Altogether we analyze six OCO-3 SAMs. We estimate the emissions of six power stations (Kendal, Kriel, Matla, Majuba, Tutuka and Grootvlei) and the largest single emitter of greenhouse gas in the world, Secunda C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Similarly, over the past decade, satellite observations of greenhouse gasses (GHGs), such as CO 2 and CH 4 , have become available and started playing a crucial role in climate mitigation monitoring ( 26 and reference therein). Recent studies have demonstrated that the combined use of satellite air quality and GHG data improves the ability of estimating surface emissions and characterizing the sources 27 29 . Combining a wide variety of satellite observations, including atmospheric concentrations and imagery data can further enhance the ability to monitor changes and attribute them to specific human and/or natural processes.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, over the past decade, satellite observations of greenhouse gasses (GHGs), such as CO 2 and CH 4 , have become available and started playing a crucial role in climate mitigation monitoring ( 26 and reference therein). Recent studies have demonstrated that the combined use of satellite air quality and GHG data improves the ability of estimating surface emissions and characterizing the sources 27 29 . Combining a wide variety of satellite observations, including atmospheric concentrations and imagery data can further enhance the ability to monitor changes and attribute them to specific human and/or natural processes.…”
Section: Introductionmentioning
confidence: 99%
“…Dedicated satellite instruments measuring backscattered sunlight in the ultraviolet-visible (UV/Vis) spectral range have provided global mapping of atmospheric NO 2 concentrations since the 1990s to quantify NO x emissions and trends, with pixel resolution down to 3.5 × 5.5 km 2 for the highest-resolution TROPOMI instrument launched in 2017 ( 1 ). This is generally too coarse to resolve individual NO x point sources except for large, isolated facilities and/or using extensive temporal averaging ( 2 7 ). Improved pixel resolution could enable fine-scale monitoring and attribution of air pollution in dense urban environments and in developing countries where pollution controls and monitoring systems are lacking.…”
mentioning
confidence: 99%